The Urgency of Defining Indonesia’s National Critical Infrastructure - Anang Setiyawan (UNIFIKASI : Jurnal Ilmu Hukum, 2019)
Abstract: Indonesia has experienced millions of cyber attacks but it has never been able to be handled properly and completely, partly because of weak policies and conventional perspectives in understanding cyber threats. A country's vital infrastructure is related to a country's national interests, so threats to vital infrastructure are tantamount to threatening Indonesia's national interests. The level of use and dependence of a country on information and communication technology is directly proportional to the level of security and defense vulnerability in a country. Communication network connectivity and information technology cause security in this domain to become a separate issue in itself. This study aims to outline the importance of Indonesia to establish a national vital infrastructure in Indonesia in order to prepare Indonesia to face threats in the fifth domain. Determination of national vital infrastructure is urgent because it is closely related to the determination of jurisdiction, national defense and security policies in the cyber domain. This research is a normative study using a comparative approach. The results showed that Indonesia still uses a conventional perspective in seeing the form of threats and determining national vital objects as stipulated in Presidential Regulation No. 63 year 2014. Therefore, in order to face the threats of defense, security as well as national interests of Indonesia in the cyber domain, government needs to evaluate existing policies in accordance with the modern threats, as well as to establish and define Indonesia's vital national infrastructure.Keywords: national interest, security, defense, critical infrastructure, cyber threat.Urgensi Penetapan Infrastruktur Vital Nasional Indonesia Abstrak: Indonesia mengalami jutaan serangan cyber namun tidak pernah dapat ditangani dengan baik dan tuntas, hal ini diantaranya disebabkan karena lemahnya kebijakan dan perspektif konvensional dalam memahami ancaman cyber. Infrastruktur vital suatu Negara sangat terkait dengan kepentingan nasional suatu Negara, sehingga ancaman terhadap infrastruktur ini sama artinya dengan mengancam kepentingan nasional Indonesia. Tingginya penggunaan dan ketergantungan suatu Negara terhadap teknologi informasi dan komunikasi berbanding lurus dengan tingkat kerentanan keamanan dan pertahanan disuatu Negara. Konektifitas jaringan komunikasi dan teknologi informasi menyebabkan keamanan di domain ini menjadi masalah tersendiri yang kompleks. Penelitian ini bertujuan untuk menguraikan pentingnya Indonesia untuk menetapkan dan mendefinisikan infratruktur vital nasional di Indonesia dalam rangka mempersiapkan Indonesia menghadapi ancaman pertahanan dan keamanan di domain kelima. Upaya penentuan infrastruktur vital nasional ini penting segera dilakukan karena berkaitan erat dengan upaya penentuan yurisdiksi, kebijakan pertahanan dan keamanan nasional Indonesia di domain. Penelitian ini merupakan penelitian normatif dengan menggunakan pendekatan komparatif. Hasil penelitian menunjukkan bahwa Indonesia masih menggunakan perspektif konvensional dalam melihat bentuk Ancaman dan menentukan objek vital nasional sebagaimana diatur dalam Peraturan Presiden No. 63 tahun 2014. Oleh karena itu, dalam rangka menghadapi ancaman pertahanan dan keamanan serta kepentingan nasional indonesia di domain cyber maka pemerintah perlu mengkaji kembali kebijakan yang ada sesuai bentuk ancaman modern dan menetapkan infrastruktur vital nasional milik Indonesia.Kata kunci: national interest, security, defense, critical infrastructure, cyber threat.